A Study on Hypertension Among Population Living Underneath Suteti and Its Related Factors Jakarta 2009 - Corrie Wawolumaya (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Hypertension  is one  of  the  degenerative  diseases which  killed  about 7,2 mill people,  about 13 % of the total death worldly.  In Indonesia  the disease has become more popular, It was  reported  that Indonesia had got a quite high prevalence of hypertension , among  male 24,9%, female 23,6% , elderly 33,3 % , SUTETI 500 kV is  the  Extra High  Electrical Energy  Transmission  lines    transferring    the   energy  from  the Electrical Power Installation   to the consumers via  the connection of Power   Relay station.  The  SUTETI electromagnetic exposure many  times  has  been  connected with  diseases  and mental  emotional  disorders  used  to  be experienced  by patients with hypertension  such as  head ache,  dizziness, easily  get angry,  heavy neck  as well  as stroke. These health disturbances  have been  considered by many  people  as SUTETI’s  negative health  impact among  people living underneath.   Most of the times were used by public as the major reasons against the installation of SUTETI wire  network.Method: The aim of study  is  to  identify  the  relation between SUTETI exposure and hypertension, and  its  related factors  among population  living underneath. Another objective  of study  is  to  identify  the  relation between mental emotional  factors and hypertension. The population was people living underneath SUTETI 0-100 ms  right and  left away  from  the  towers. The number  of  samples  collected was  about 2000  people with  the calculated  sample size 753 and were stratified  into  three zones, zone 1  , 0-30 ms  right and  left  from  the  tower, zone 2  , 30-70 ms and  zone 3  ,70-100 ms.  The  independent  variables   were sociodemographic  factors  i.e.,  age,  sex,  education, income  ,  length of stay at home, duration of stay at  the  location, besides smoking habit, annoyance, satisfaction, electrical  field dose  , magnetic  field dose  and zone  .   Blood chemistry examined were  cholesterol and nutritional status  besides melatonin, mental emotional  and  sleeping  disorders.Result  and  conclusions: Study  results  reported  that  the  highest  outside  the  house measurements  of  the electric  field was  in zone 1  ,   3,2 kV/m   and magnetic  field   was     6,7 X 10-² mT  , both were still  lower  than  the National Standard of SUTETI in  Indonesia  – SNI 2003 , 5 kV/m and 0,1 mT. The prevalence of hypertension based on  zone were  significant  ,  zone 1,  14,14%, zone  2  ,   11,31%  and zone  3,  5,66 %  (   p  =  0,004)   The  logistic regression  function analysis  identified  two determinants, duration of  stay  ( p =  0,044  )  ; OR 3,85  (95 %CI  :1,04 – 14, 12) ; income ( p = 0,019 , OR  15, 891 ( 95% CI: 1,578 – 169,97). People living > 30 years under the SUTETI towers  (0  – 100ms  ) will  be  risky  3,85  times  to get  hypertension  than  people  living  less  than  30  years. Also people with less income had the risk 16 times to get hypertension compared to middle income. The results did not reveal  any  specific  evidence  of  association  between  the  electromagnetic  exposure  and  hypertension.  The logistic  regression  function  also  did  not  identify  any  association  between mental  emotional  disorders  and sleeping  disorders  towards  hypertension.Keywords:    hypertension, SUTETI, mental emotional  disorders